(untitled) (Texas Journal of Engineering and Technology, 2025)
This article evaluates the effectiveness of ultrasonic technology in controlling pest insects under greenhouse conditions. The mechanism of ultrasonic wave impact on insects, as well as its effects on their movement and reproduction processes, is analyzed. Experimental studies have shown that ultrasonic signals in the 30–50 kHz range demonstrate high efficacy against certain pests. This method can be considered an environmentally friendly and pesticide-free alternative for pest control.